Insiders and Outsiders: Construction ofIdentity Among Youth Travellers in Whistler British Columbia - Hayes, Nicole (My University, 2001)
Whistler is a popular tourist resort set in the heart of the Coast Mountains of British Columbia. Among the many people who are attracted to Whistler every year are the youth travellers who come to work in the resort for a season while they ski its slopes and mountain bike its trails. Youth travellers are extremely conscious of their identity as residents and dissociate themselves from tourists and others more recently arrived or more transient than themselves. Nevertheless, the boundaries between tourists, youth travellers and locals are very fluid in Whistler. I argue that youth travellers experience this instability as a threat to their identity and respond symbolically through "disidentification" with others and a manipulation of insider-outsider dichotomies. An analysis of youth travellers in Whistler reveals that their need to reinforce the boundaries between themselves and others is reflected in their perceptions of Whistler, tourists, fellow youth travellers, and the "extreme."
Keywords: Anthropology; Anthropology